Sosialisasi Penggunaan Metode Pembayaran Elektronik/Digital di Kecamatan Petir Serang-Banten - Aan Ansori (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study aims to identify the level of digital literacy among the residents of Tambiluk Village and provide education on the use of electronic payment tools. Tambiluk Village, located in Petir Subdistrict, Serang Regency-Banten, was chosen as the location for community outreach activities. Based on an initial survey, the village residents already use smartphones for various activities, but have not yet fully integrated them into the digital system. Many residents still lack understanding of the benefits of digitalization, particularly in financial transactions. This outreach program targeted village officials and was conducted on December 15, 2023. The methods used included lectures to provide in-depth knowledge about the development of digital payment tools, as well as hands-on practice sessions. The results of this program showed an improvement in the understanding and skills of village officials in utilizing digital technology. In conclusion, this outreach program had a positive impact on enhancing the digital literacy of the community, especially in adopting cashless transactions. The education and training provided are expected to drive digital transformation in Tambiluk Village as a whole, thereby increasing efficiency in various daily activities.